Analysis of transparency and accountability in financial management (Case study at Don Bosco Foundation Manado) - Napan, Lambertus; Morasa, Jenny; Gamaliel, Hendrik (The Contrarian : Finance, Accounting, and Business Research, 2025)
The purpose of this study is to examine the implementation of financial management transparency and accountability at the Don Bosco Foundation in Manado. This research uses a descriptive quantitative method, along with a qualitative approach to understand the perspectives and experiences of individuals or groups. The research instruments include questionnaires and interviews with ten informants. Data analysis involves both descriptive quantitative analysis and qualitative analysis using triangulation of interview data. The findings show that financial management transparency at the Don Bosco Foundation is rated as medium, meaning the foundation generally practices good transparency in policy-making for managing the educational institution. Financial management accountability is rated as high, indicating that the foundation's accountability practices are very strong. This demonstrates that the foundation is highly accountable in managing the public entity, earning trust from the community now and in the future. Overall, financial management at the Don Bosco Foundation is rated as high, showing that it is well-aligned with the Work Plan and Budget, and is properly managed and accounted for.